Time value of money in the Lithuanian credit market: A practical analysis of consumer loan offers - Mantė Pryšmantaitė; Astijus Markauskas; Jekaterina Kartašova (Agora International Journal of Economical Sciences (AIJES), 2025)
This report uses the Time Value of Money (TVM) framework to evaluate and compare consumer loan offers from three Lithuanian credit providers: Inbank, Artea, and Saldo Bank. Focusing on a loan amount of exteuro5000, the study examines repayment terms of 12, 24, and 36 months, each with different interest rates and administrative fees. By calculating key financial indicators such as monthly payments (PMT), total repayment, total interest paid, and present value (PV), the analysis identifies differences in the actual cost of borrowing. The results show that Inbank offers the most financially favorable terms overall, yet borrowers may still choose more expensive options based on short-term affordability. These findings emphasize the value of using TVM principles in personal finance and highlight the importance of transparent loan structures in helping consumers make informed financial decisions in the Lithuanian credit market.
Keywords: 330; TVM; consumer loans; Lithuanian credit market; personal finance